Visits to national parks : effects of park characteristics and spatial demand - Neuvonen, Marjo; Pouta, Eija; Puustinen, Jenni; Sievänen, Tuija (Elsevier, 2010)
Understanding the relationship between the number of visits to national parks and their characteristics is crucial for park planning and management. Visitation has a key role in existing national parks, but also in assessing the social and economic impacts of new parks. This study examined how the natural characteristics of a park, the recreation facilities and services inside a park and tourist services in surrounding communities, as well as the park's location in relation to the population, are associated with the number of visits. Regression modelling was used to analyse the visitation to thirty-five national parks in Finland. The results demonstrated that recreation opportunities, the number of biotopes, the provision of trails and the park's age increase the number of visits, while the park location in relation to the population only has a significant effect in southern Finland. The results imply the dual role of national parks as resource-based destinations if the natural characteristics are outstanding, but also as more user-oriented areas fulfilling recreation needs in the most populated parts of the country.
Keywords: Ma; kysyntäennuste; kysyntämallit; luonnon virkistyskäytön kysyntätekijät; luontomatkailu; suojelualueet; tarjontatekijät; kansallispuistot; luontomatkailu; retkeily; luonnon virkistyskäyttö; ulkoilualueet; retkeilyalueet; virkistysalueet; demand factors; nature tourism; protected areas; supply factors; visitor model; visit prediction